Propriedades da matéria-prima e da massa de farinha de trigo elaborada pela reincorporação de farelo de granulometria fina - Boita, Elis Regina de Fátima (2015)
The beneficial effects of consumption of baking goods made with whole wheat flour are known, but the limited acceptance due to lower volume, thicker texture and hardness. To minimize the effects of the bran in technological characteristics is necessary to consider new ways of whole wheat flour production. The objective of this work was to study the properties of raw materials and of the dough of wheat flour elaborate by the reincorporation of gran of fine granulometry and elaboration of loaf bread. Wheat was submitted at grinding in an industrial mill, obtaining the flour fraction, semolina and bran. The bran was subjected to new grinding, homogenized with semolina fraction and reincorporated in flour at the concentrations of 0%, 25%, 50%, 75% and 100%. Samples from each treatment were packed in raffia bags and stored in cold storage until the completion of laboratory tests. The experiment was designed in randomized order with use of five treatments and accomplished the analyzed in triplicate, proximate chemical composition, grain size, color, damaged starch, falling number, gluten, rapid analysis of viscosity, alveography, farinography, volume fermentation resistance to extension, extensibility and baking test. In the loaf breads were carried out the specific volume assessments, firmness, moisture content, crust color and crumb color. The sgnificance of data was tested by the analysis of variance and in significant models means compared each other by the Tukey test at 95% confidence interval. The chemical composition influences the technological characteristics of flours in proportion with the reincorporation of bran of fine granulometry. The reduction of bran particle size minimizes the negative effects exerted in dough rheology. Pasting properties of flours diminish proportionally with the increase bran content, attributed to the increased absorption of water by the fibers, present in greater quantity and low starch content. The specific volume decreases with increasing content of the bran samples. The firmness and moisture values influence the shelf life can be used as indicators of technological quality in loaves of bread. The characteristics observed in flour with incorporation of bran of fine granulometry can be attributed in greater extension by dilution effect of protein matrix caused by fibers. More results of the effect of particle size about wholemeal dough properties and quality of baking products still need to be investigated